Work Organization and Professionalization in New Media Industry – The Case of a Finnish Company - Haapakorpi, Arja (Nordic Journal of Working Life Studies, 2012)
The article explores work organization in one new media company in a turning point of the business, in the 2000s. The company had changed from a small workshop to a medium-sized company in a few years. Growth, increasing competition, and uncertainty of profitability had altered the management and work organization. An approach of governance, aimed at efficiency and economy, was systematically implemented; the working methods were standardized, strict division of labor was carried out, and the professional qualifications were mainstreamed according to the business. The professional employees appreciated the new business-like management, but discovered that their opportunities for creative work were diminished with decreasing resources and a new project management pattern.